2010
DOI: 10.3945/jn.109.111740
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Multiple Micronutrient Supplementation Has Limited Impact on Micronutrient Status of Bangladeshi Infants Compared with Standard Iron andFolic Acid Supplementation1–3

Abstract: Knowledge about the impact of maternal food and micronutrient supplementation on infant micronutrient status is limited. We examined the effect of maternal food and micronutrient supplementation on infant micronutrient status in the Maternal and Infant Nutrition Interventions in Matlab Trial. Pregnant women (n = 4436) were randomized to Early or Usual promotion of enrollment in a food supplementation program. In addition, they were randomly allocated to 1 of the following 3 types of daily micronutrient supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
2
33
1
5
Order By: Relevance
“…More recently, Meenakshi et al (2010) concluded that overall, biofortification can make a significant impact on reducing the burden of micronutrient deficiencies in the developing world in a highly cost-effective manner; however, the impacts differ depending on the combination of crop, micronutrient and country, and the major reasons underlying these differences are identified to inform policy. In the past, food fortification, diet diversification, and nutrient supplementation have been most frequently used as public health interventions to reduce micronutrient-induced morbidity and mortality worldwide (Suharno et al 1993;Haider et al 2003;Brown et al 2007;Wienecke and Gruenwald 2007;Casey et al 2010;Eneroth et al 2010). However, these approaches have had only limited success and could not by themselves attain sufficiently millennium development goals mainly because such interventions require infrastructure, continuous flow of resources, purchasing power, or access to markets and health care systems to their success, often not available to people living in remote areas (Underwood 1999;Imhoff-Kunsch et al 2007;Ssemakula and Pfeiffer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Meenakshi et al (2010) concluded that overall, biofortification can make a significant impact on reducing the burden of micronutrient deficiencies in the developing world in a highly cost-effective manner; however, the impacts differ depending on the combination of crop, micronutrient and country, and the major reasons underlying these differences are identified to inform policy. In the past, food fortification, diet diversification, and nutrient supplementation have been most frequently used as public health interventions to reduce micronutrient-induced morbidity and mortality worldwide (Suharno et al 1993;Haider et al 2003;Brown et al 2007;Wienecke and Gruenwald 2007;Casey et al 2010;Eneroth et al 2010). However, these approaches have had only limited success and could not by themselves attain sufficiently millennium development goals mainly because such interventions require infrastructure, continuous flow of resources, purchasing power, or access to markets and health care systems to their success, often not available to people living in remote areas (Underwood 1999;Imhoff-Kunsch et al 2007;Ssemakula and Pfeiffer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…En la mayoría de los países industrializados también se recomienda el aporte complementario de hierro sistemático durante el embarazo, aunque existen menos datos a favor de que mejore los desenlaces maternos o fetales [117,118] . En estudios recientes se deja entrever que dosis menores de 30 mg de hierro/día pueden ser tan eficaces como la dosis actualmente recomendada de 60 mg/día, con respecto al estado de hierro materno y del lactante [116,119,120] . En países de rentas bajas se ha demostrado que el aporte complementario de múltiples micronutrientes durante el embarazo es tan eficaz como el de 129 hierro/ácido fólico solo en reducir la anemia en mujeres gestantes [116,121] .…”
Section: Prevención De La Ch Como Parte De Programas Integrados De Saunclassified
“…The MINIMAT trial in Matlab reported multiple micronutrient supplementation with the recommended dietary allowances (RDA) (2.6 µg/d B12 in pregnancy up to 3 months postpartum) did not significantly impact on maternal B12 deficiency. However it only reduced infant deficiency at 6 mo to 26% [83]. In a randomized, placebo-controlled trial in Tanzania, multivitamin supplementation (with 50 µg B12) of HIV-infected mothers (n=716) throughout pregnancy upto 6 months postpartum significantly increased infant plasma vitamin B12 concentrations at age 6 weeks and 6 months (mean differences:176 and 127 pmol/l, respectively) and decreased the prevalence of vitamin B12 deficiency compared to the placebo [84].…”
Section: Citationmentioning
confidence: 99%
“…Eneroth H et al [83] RCT in Bangladesh, n=4436 (GW ≥14). Daily micronutrient supplements either: 1) folic acid and 30 mg iron; Fe30Fol or 2) folic acid and 60 mg iron; or 3) a multiple micronutrient including folic acid and 30 mg iron (MMS).…”
Section: Conclusion and Limitationmentioning
confidence: 99%